2018
DOI: 10.1111/een.12671
|View full text |Cite
|
Sign up to set email alerts
|

Agri‐environmental schemes affect the trophic niche size and diet of common carabid species in agricultural landscapes

Abstract: 1. Carabids are abundant in agroecosystems and provide biocontrol services by feeding on weed seeds and pests. We compare the effects of two fundamentally different agri-environmental schemes (AES) on the numeric and trophic responses of four common carabid species: Anchomenus dorsalis, Poecilus cupreus, Pseudoophonus rufipes and Pterostichus melanarius.2. In six cereal fields under organic farming and six sown flowering fields, 10 290 individuals of the four species were sampled to quantify their numeric resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 111 publications
(196 reference statements)
0
7
0
Order By: Relevance
“…All ants are eusocial insects that depend on stable, usually large and long-lived, permanent nests (Höldobler and Wilson, 2009). Hence, its sensitivity to management in periodically disturbed systems such as croplands would be stronger than sensitivity of the short-lived or solitary arthropod groups best studied to date, bees, butterflies or carabids, mainly (Albrecht et al, 2020;Batáry et al, 2011;Mader et al, 2018Mader et al, , 2017Martin et al, 2019;Scheper et al, 2013), which could be more sensitive to year-to-year weather fluctuations (Pollard, 1991;Roy et al, 2001) and less indicative of background trends.…”
Section: Introductionmentioning
confidence: 99%
“…All ants are eusocial insects that depend on stable, usually large and long-lived, permanent nests (Höldobler and Wilson, 2009). Hence, its sensitivity to management in periodically disturbed systems such as croplands would be stronger than sensitivity of the short-lived or solitary arthropod groups best studied to date, bees, butterflies or carabids, mainly (Albrecht et al, 2020;Batáry et al, 2011;Mader et al, 2018Mader et al, , 2017Martin et al, 2019;Scheper et al, 2013), which could be more sensitive to year-to-year weather fluctuations (Pollard, 1991;Roy et al, 2001) and less indicative of background trends.…”
Section: Introductionmentioning
confidence: 99%
“…Ground beetles are the few families of Coleoptera widespread in biotopes, which experience various types of anthropogenic influence [11][12][13][14][15][16][17][18][19]. This paper presents the analysis of the species composition and ecological structure of ground beetle complexes in windfalls and in the areas not affected by this type of impact.…”
Section: Resultsmentioning
confidence: 99%
“…As for diet contribution, beetles A. dorsalis were observed incorporating more plant-based resources in organically managed cereal fields than in the flowering fields (Mader et al 2018). The study (Pajač Živković et al 2018) showed the positive effect of exclusion nets on A. dorsalis in an apple orchard of Croatia, thus confirming their value in assessing the introduction of new agricultural measures into practice.…”
Section: Discussionmentioning
confidence: 99%